PESAN MORAL ISLAMISASI ILMU PENGETAHUAN DAN TEKNOLOGI DALAM PANDANGAN ABDUS SALAM DAN AHMAD BAIQUNI - Julita Lestari (JURNAL AL-AQIDAH, 2022)
This study aims to describe the discourse of Islamization of science and technology which was initiated by Abdus Salam and Ahmad Baiquni. This research is qualitative by using exploratory method and content analysis. The results of the research found that the discourse of Islamization initiated by Abdus Salam is trying to develop and conquer technology with the basic principle of monotheism, that all knowledge originates from one substance. Meanwhile, according to Ahmad Baiquni, the Islamization of science is an attempt to refer back to the Qur'an as the source of everything, such as a source for science and technology. The moral message that can be gleaned from the discourse on the Islamization of science developed by Abdus Salam is that the source of knowledge is the One and Only One, namely Allah SWT. The more we dive into the knowledge, the deeper our belief in the Creator should be. Meanwhile, from the discourse of Islamization of knowledge and technology, Ahmad Baiquni can realize that in order to know and develop science and technology, the thing that humans can do is approach the Koran. Because the Koran is the source of knowledge it self.